Does leaving school in an economic downturn impact access to employer-sponsored health insurance? - Johanna Maclean (IZA Journal of Labor Policy, 2014)
Previous work documents that leaving school in an economic downturn persistently depresses career outcomes as measured by wages, earnings, and other markers of labor market success. In this study I test whether leaving school in an economic downturn influences access to employer-sponsored health insurance. Using a long panel of workers drawn from the National Longitudinal Survey of Youth 1979 Cohort, I model the likelihood that a worker has access to employer-sponsored health insurance from initial labor market entrance through mid-career. I address the potential endogeneity of time and location of school-leaving with instrumental variables. My results suggest that leaving school in an economic downturn lowers the probability of access to employer-sponsored health insurance and this disparity is statistically distinguishable from zero 18 years after school-leaving.
Keywords: I1; I12; J3; 330; Employer-sponsored health insurance; Fringe benefits; School-leaving; Macroeconomic fluctuations